2015
DOI: 10.1016/j.stem.2015.05.003
|View full text |Cite|
|
Sign up to set email alerts
|

Functionally Distinct Subsets of Lineage-Biased Multipotent Progenitors Control Blood Production in Normal and Regenerative Conditions

Abstract: SUMMARY Despite great advances in understanding the mechanisms underlying blood production, lineage specification at the level of multipotent progenitors (MPPs) remains poorly understood. Here, we show that MPP2 and MPP3 are distinct myeloid-biased MPP subsets that work together with lymphoid-primed MPP4 cells to control blood production. We find that all MPPs are produced in parallel by hematopoietic stem cells (HSCs), but with different kinetics and at variable levels depending on hematopoietic demands. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
621
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 539 publications
(696 citation statements)
references
References 41 publications
54
621
1
1
Order By: Relevance
“…Markers for LT-HSCs, ST-HSCs, and MPP1-MPP4 are previously described. 14,25,26 In cell proliferation assays, intracellular staining of allophycocyanin-conjugated anti-BrdU and 7-aminoactinomycin D (7-AAD) were performed following surface staining. Stained cells were analyzed on a BD Fortessa flow cytometer.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Markers for LT-HSCs, ST-HSCs, and MPP1-MPP4 are previously described. 14,25,26 In cell proliferation assays, intracellular staining of allophycocyanin-conjugated anti-BrdU and 7-aminoactinomycin D (7-AAD) were performed following surface staining. Stained cells were analyzed on a BD Fortessa flow cytometer.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…7,11,13,14 these subtypes were impacted by flagellin treatment, we performed flow cytometry analysis on LSK cells from flagellin-or PBS-treated WT B6 mice using the recently defined signaling lymphocytic activation molecule (SLAM) code, which is capable of distinguishing LT-HSC, ST-HSC, and MPP subtypes. 14,25,26 This cellular identification protocol indicated that flagellin did not increase the level or alter the proliferative status of LT-HSCs (supplemental Figure 7A-C). Rather, flagellin treatment drove the proliferation of ST-HSCs and myeloid precursors MPP2 and especially MPP3, whose levels increased 10-fold following flagellin treatment ( Figure 5A-E).…”
Section: Flagellin Treatment Preferentially Induces Hematopoietic Promentioning
confidence: 99%
See 2 more Smart Citations
“…She showed that during blood regeneration, HSCs are induced to overproduce myeloid-biased multipotent progenitors (Pietras et al, 2015). An important consequence of the activation of this myeloid regeneration axis is the formation of defined granulocyte/ macrophage progenitor clusters in the bone marrow cavity, which drive the local overproduction of granulocytes.…”
Section: Understanding and Mimicking The Nichementioning
confidence: 99%